Long-term hematological response in 5q- syndrome after lenalidomide suspension and further improvement by deferasirox. - Pasquale Niscola (Mediterranean Journal of Hematology and Infectious Diseases)
The long-term hematological response in a patient with 5q- syndrome after lenalidomide suspension and the further improvement observe while she was receiving deferasirox alone is reported.